The Effect of Reliability, Service Price, Guarantee, Organization Image and Responsiveness on Customer Satisfaction and Customer Loyalty on The Freight Forwarding Service Company PT Lookman - Cienthia Dewi Lookman (Universitas Ciputra Surabaya, 2022)
PT Lookman Djaja is a trucking delivery service company that has been serving Business-to-Business (B2B) consumers, especially in Java, Sumatra, Bali, Lombok to NTB. To be able to exist for more than 35 years in a highly competitive industry is certainly quite demanding, not to mention very challenging. However, it is undeniable that PT Lookman Djaja has been affected from both outside and within the industry. The economic downturn since the COVID-19 pandemic coupled with intense competition from competitors and substitute services have overwhelmed the company. Furthermore, the number of consumer contracts has also decreased in the past year. This study is conducted to examine and analyze the effect of Reliability, Service Price, Guarantee, Organization Image and Responsiveness on Customer Satisfaction and Customer Loyalty in PT Lookman Djaja. This study is conducted for 7 months from December 2021 to June 2022. The population of this study is all B2B (Business to Business) consumers from the company, totaling 307 consumers throughout 2021. The research sample used in this study is 47 respondents determined by using purposive sampling technique. The analytical method used is Partial Least Square Structural Equation Modeling (SEM-PLS) and processed using the smartPLS 3 program. The result of this study indicates that the variables Reliability, Service Price and Guarantee have no effect on Customer Satisfaction, however Organization Image and Responsiveness have a significant effect on Customer Satisfaction in PT Lookman Djaja. In addition, this study also indicates that Customer Satisfaction has a significant effect on Customer Loyalty in PT Lookman Djaja.